2021
DOI: 10.36941/ajis-2021-0142
|View full text |Cite
|
Sign up to set email alerts
|

On-Site and Hybrid Workplace Culture of Positivity and Effectiveness: Case Study from Austria

Abstract: Workplace culture includes beliefs, attitudes, practices, rules, norms and customs. Ideal workplace culture focuses on activities that generate and demonstrate trust. A strong form of essential values that all employees respect and practice helps to build the positivity and effectiveness of a workplace environment. This paper examines the positivity and effectiveness of an on-site and hybrid working model from Austria. A research question is raised that concerns the difference between negative and positive app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 11 publications
0
17
0
2
Order By: Relevance
“…4,15,19 Such reasoning would conclude that remote working is not suited to all individuals, and the positive and negative impacts of WFH is largely dictated by unique traits as personal characteristics and preferences. Nevertheless, supporting literature suggests hybrid WFH models have the potential to positively impact mental health 21,22 as well as provide societal benefits. 23 Therefore, it is recommended to consider utilizing flexible work schedules that allow employees to work in their preferred environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,15,19 Such reasoning would conclude that remote working is not suited to all individuals, and the positive and negative impacts of WFH is largely dictated by unique traits as personal characteristics and preferences. Nevertheless, supporting literature suggests hybrid WFH models have the potential to positively impact mental health 21,22 as well as provide societal benefits. 23 Therefore, it is recommended to consider utilizing flexible work schedules that allow employees to work in their preferred environment.…”
Section: Discussionmentioning
confidence: 99%
“…21 When comparing the effects of working in either a hybrid model or a traditional cubicle office space, one Austrian study found those working within a hybrid model noted higher positive values, such as support, care, and forgiveness compared to participants working exclusively on-site. 22 The study suggested a balanced work environment can exert a protective effect on one's mental health. 22 Implementing more flexible work schedules through a hybrid model may also encourage older employees to extend their retirement dates and expand employment options for people with physical impairments.…”
Section: Harmful Factors Of Mental Health and Lifestyle In Wfhmentioning
confidence: 98%
See 1 more Smart Citation
“…Inevitably the people are now supposed to live and work in a volatile, uncertain, complex, and ambiguous (VUCA) world (Hänti et al, 2021) and this was well confirmed with the outbreak of COVID 19 pandemic (Murugan et al, 2020). COVID-19 has been a turning point; especially in businesses since e-working which was practicing even before the pandemic but at a smaller scale, came to practice along with many other changes impacting traditional practices (Beno, 2021;Mariniello et al, 2021). Hybrid work model (HWM) is found as a mixture of working remotely (From anywhere except the office) and in-person (Beno & Hvorecky, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Though many studies conducted to explain the hybrid working model adoption behavior (Iqbal, Khalid, & Barykin, 2021;Lenka, 2021;Skountridaki, Marks, & Mallett, 2021;Williamson, & Colley, 2022), still determinant's of intention to adopt HWM by executive level employees seems to be a grey area that is open for further studies. Especially when it comes to developing countries like Sri Lanka very little research is carried out and it is rather challenging to generalize the findings of the studies conducted in other contexts due to the economic, social, cultural and technological differences between the developed and Sri Lankan context (Beno, 2021;Gensler Research Institute, 2020).…”
Section: Introductionmentioning
confidence: 99%